Measurement of emotional intelligence in students of two public educational institutions in two different social contexts - Torres Azcárate, Adriana Sofía; Núñez Bernal, Carlos Alberto; Roncancio Moreno, Mónica (Universidad Pontificia Bolivariana, 2020)
The main objective of this article is to perform a comparative analysis of perceived emotional intelligence (EI) in a group of 198 vocational media students from the city of Palmira, belonging to two different contexts (urban and rural) in order to know the influence of context on students’ emotional intelligence. It is a quantitative investigation of descriptive character; the TMMS24 test and the SPSS statistical program were used. The results showed that there are no significant differences in the emotional intelligence perceived in the two contexts or between the genders. Within the three components of the EI (attention, clarity and repair) significant differences were found in the dimension of emotional attention, being higher in the students of the rural area as well as higher in the women than in the men, although all the scores Averages obtained by the two populations are considered adequate. We can conclude that the context is not a factor that completely limits the development of EI